ESTIMASI DAN FAKTOR-FAKTOR YANG MEMENGARUHI EFISIENSI BANK DOMESTIK DAN ASING DI INDONESIA - Fathony, Moch. (Jurnal Keuangan dan Perbankan, 2012)
The objective of this study was to evaluate the performance of the technical efficiency of domestic banks andforeign banks in Indonesia during the period 2008-2009 using a two-stage analysis. The first phase of testingusing the method of Data Envelopment Analysis (DEA) showed that foreign-owned banks efficiently producedhigher performance than domestic-owned banks. The second phase of testing showed that the size of the bank,the net interest margin (NIM), and non-performing loans (NPL), had a positive and significant effect on theperformance efficiency of the domestic and foreign banks. Return on assets (ROA) had a positive but notsignificant effect on the performance efficiency of domestic banks. While for foreign banks, ROA had a positiveand significant effect on performance efficiency. The capital adequacy ratio (CAR) had a positive and signifi-cant effect on the performance efficiency of domestic banks, while for foreign banks, the CAR had positive butnot significant effect on performance efficiency. Operational costs had a significant negative influence on theperformance efficiency of the domestic and foreign banks.